Determinasi Karakteristik Pemerintah Daerah Terhadap Opini BPK - Destin Alfianika Maharani; Anastasia Anggarkusuma Arofah (Jurnal Akuntansi Keuangan dan Bisnis, 2021)
The research objectives were to determine: 1). Effect of government size on BPK opinion 2). The influence of the level of regional dependence on the center on the BPK opinion, 3) The influence of level of prosperity on the BPK opinion, 4) The influence of the level of regional independence on the BPK opinion. The population in this study were districts and cities in Central Java for 2017 to 2019. The samples in this study used purposive sampling and logistic regression analysis methods. The test instrument used in this study used SPSS version 24. Partially, the size of government size has a negative and significant effect on BPK's opinion. The variables of the level of regional dependence on the central government and the level of prosperity have a positive and significant effect on BPK's audit opinion. Meanwhile, the level of regional dependence has a negative and insignificant effect on BPK's opinion